Evaluation measure of 3d volumetry of masseter hypertrophy: association with modalities of imaging - Pinto, Antonione Santos Bezerra; GalvÃo, Neiandro Dos Santos; Mendes, Jean De Pinho; Pinto, Paulo Henrique Viana; Lopes, Sérgio Lúcio Pereira De Castro; Costa, André Luiz Ferreira (Faculdade São Leopoldo Mandic, 2018)
Abstract Masseteric hypertrophy is a benign condition, asymptomatic and rare, characterized by the excessive development of the masseter muscle, which usually results in aesthetic complaints. The imaging exams for differential diagnosis of pathologies in the parotid-masseteric region is always recommended. This work aims the imaging characterization of masseteric hypertrophy through the report of two clinical cases combining different imaging modalities: panoramic radiography, magnetic resonance imaging, computed tomography, ultrasonography and 3D volumetry. Two male subjects with no family history of masseteric hypertrophy were referred to a diagnostic center in dentomaxillofacial radiology due to an increase in bilateral facial volume in the masseteric region. Images of the panoramic radiography showed an increase of the bilateral mandibular angle in both cases. Using computerized tomography, bilateral masseter muscle hypertrophy was demonstrated in the patients, and magnetic resonance scan and ultrasound examination were performed for better visualization and muscle measurement. 3D volumetry assessment of musculature showed as additional tool to evaluate the status of the masseter muscles in patients with Masseteric hypertrophy. Therefore, the association of imaging examinations allowed to perform the imaging characterization of masseteric hypertrophy with presence of bone exostosis.

RESUMO A hipertrofia massetérica é uma condição benigna, assintomática e rara, caracterizada pelo desenvolvimento excessivo do músculo masseter, que geralmente resulta em queixas estéticas. São sempre recomendados os exames de imagem para diagnóstico diferencial de patologias na região parotídea-massetérica. Neste trabalho objetiva-se a caracterização da imagem da hipertrofia massetérica através do relato de dois casos clínicos combinando diferentes modalidades de imagem: radiografia panorâmica, ressonância magnética, tomografia computadorizada, ultra-sonografia e volumetria 3D. Dois indivíduos do sexo masculino sem história familiar de hipertrofia massetérica foram encaminhados para um centro de diagnóstico em radiologia dentomaxilofacial devido ao aumento do volume facial bilateral na região massetérica. As imagens da radiografia panorâmica mostraram um aumento do ângulo mandibular bilateral em ambos os casos. Usando tomografia computadorizada, foi demonstrada hipertrofia muscular massetérica bilateral nos pacientes, e a varredura de ressonância magnética e ultra-sonografia foram realizadas para melhor visualização e medição. A avaliação volumétrica em 3D da musculatura mostrou-se como ferramenta adicional para avaliar o estado dos músculos masseteros em pacientes com hipertrofia massetérica. Portanto, a associação de exames de imagem permitiu realizar a caracterização da imagem da hipertrofia massetérica com presença de exostose óssea.
Avaliação de medidas volumétricas 3D da hipertrofia massetérica em dois casos: associação com modalidades de imagem
Keywords: Diagnostic imaging; Hypertrophy; Masseter muscle; Radiology; Diagnóstico por imagem; Hipertrofia; Músculo masseter; Radiologia